(untitled) (Journal of Computational Mathematics, 2000)
The abstract L^2-norm error estimate of nonconforming finite element method is established. The uniformly L^2-norm error estimate is obtained for the nonconforming finite element method for the second order elliptic problem with the lowest regularity, i.e., in the case that the solution u∈H^1(Ω) only. It is also shown that the L^2-norm error bound we obtained is one order higher than the energe-norm error bound.